2012
DOI: 10.1097/yic.0b013e32834fc431
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of risperidone oral solution and intramuscular haloperidol with the latter shifting to oral therapy for the treatment of acute agitation in patients with schizophrenia

Abstract: This randomized, parallel-group, open study investigated the efficacy and safety of risperidone oral solution (RIS-OS) in combination with clonazepam and intramuscular haloperidol for the treatment of acute agitation in patients with schizophrenia, and the study explored the possibility of decreasing the efficacy of an acute 6-week treatment by switching intramuscular haloperidol injection to RIS-OS. Two hundred and five agitation-exhibiting schizophrenic inpatients at six hospitals were originally included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 0 publications
1
28
0
5
Order By: Relevance
“…(Meehan et al ., ; Zimbroff et al ., ). Three trials employed a combined treatment approach: one assessed the use of risperidone with lorazepam (Currier et al ., ), one risperidone with clonazepam (Fang et al ., ) and two trials used haloperidol with lorazepam(Currier et al ., ; Hwang et al ., ). The trials assessing inhaled loxapine (Allen et al ., ; Lesem et al ., ; Kwentus et al ., ) all included two dose sizes of loxapine (5 mg and 10 mg), a range of dose sizes of olanzapine were included in another trial (Breier et al ., ) whilst a range of doses of aripiprazole were included in a third trial (Tran‐Johnson et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…(Meehan et al ., ; Zimbroff et al ., ). Three trials employed a combined treatment approach: one assessed the use of risperidone with lorazepam (Currier et al ., ), one risperidone with clonazepam (Fang et al ., ) and two trials used haloperidol with lorazepam(Currier et al ., ; Hwang et al ., ). The trials assessing inhaled loxapine (Allen et al ., ; Lesem et al ., ; Kwentus et al ., ) all included two dose sizes of loxapine (5 mg and 10 mg), a range of dose sizes of olanzapine were included in another trial (Breier et al ., ) whilst a range of doses of aripiprazole were included in a third trial (Tran‐Johnson et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Two controlled trials over 5 days also reported no difference between oral aripiprazole and oral olanzapine 14 and between oral risperidone and intramuscular haloperidol. 11 Likewise, an observational, nonrandomized study in a mixed psychiatric emergency population failed to find differences between olanzapine, risperidone, and haloperidol over 5 days. 24 In contrast, longer trials seem to favor olanzapine.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of agitation as measured with the PANSS-EC is in the same range as reported in 1 controlled trial and 3 observational studies 10,13,24,27 but clearly higher than in most controlled trials. 11,12,14 We have used higher PANSS cutoff scores for inclusion than the cutoff used in most other studies.…”
Section: Y13mentioning
confidence: 99%
See 2 more Smart Citations